TITIK TEMU MAKNA BAPTISAN MENURUT ROMA 6:3-6 DAN KONSEP MANUNGGALING KAWULO GUSTI BAGI PEMURIDAN KONTEKSTUAL MASYARAKAT JAWA - Aji Suseno; Yehudha Andrew Sugito; Eko Wahyu Suryaningsih (Manna Rafflesia, 2024)
Baptism and discipleship are two things that cannot be separated. In the Great Commission of the Lord Jesus, they are intertwined. One of the concepts contained in baptism is union with Christ found in Romans 6:3-6. This is an important theme that believers must understand, especially through discipleship. On the other hand, the author sees the dominance of the Javanese tribe among the Indonesian population. This dominance occurs in the government, economic sectors, and church life. This fact drives this research to actualize contextual discipleship carried out by the Church towards Javanese congregations. One of the concepts of Javanese thought with a common theme of human unity with God is the concept of manunggaling kawulo gusti. Through the literature research method, this concept is explored in depth. This exploration will be seen and interpreted from the baptism perspective in Romans 6:3-6. As a result, there are points of convergence as well as points of difference. The findings obtained will then become material for the actualization of contextual discipleship in Javanese society.